급성 메탄올과 에틸렌글리콜 중독 환자의 특성: 일개 중독분석실 농도 분석 - 박민경; Min Kyung Park; 응급취약지지역협력팀; Emergency Vulnerable Area Regional Cooperation Team; 이아름; Arum Lee; 김미숙; Misuk Kim; 김윤희; Yun Hee Kim; 고정인; Jung-in Ko; et al. (대한임상독성학회지, 2025)
Purpose: Toxic alcohol exposures are rare yet remain an ongoing and potentially lethal poisoning problem in Korea. Few studies have characterized the epidemiological features and blood substance levels in acutely intoxicated patients presenting to emergency departments (EDs). The objective of this study was to describe the characteristics of intoxicated patients for whom toxicological analyses were requested. Methods: We reviewed demographic and analytical data from a toxicological laboratory operated by the National Medical Center between 2018 and 2022. In total, 1,244 cases from 35 EDs were analyzed. Results: Of the analyzed cases, 108 cases (63 patients) tested positive for toxic alcohols, including methanol (MeOH), ethylene glycol (EG), and isopropyl alcohol. Sixty patients had a single toxic alcohol detected: 17 with MeOH and 43 with EG. Clinical features included a median age of 42 years, 63.3% male, 100% acute exposure events, 66.7% suicide attempts, and 50.0% ethanol co-ingestion. Median ingestion amounts were 255 mL (MeOH) and 365 mL (EG). Significant differences between MeOH and EG groups included ingestion of an unknown substance (41.2% vs. 69.8%, p=0.04), initial blood pH (7.33 vs. 7.20, p<0.01), and multiple substance ingestion (52.9% vs. 81.4%, p=0.03). Median blood concentrations were 255 mg/dL (MeOH) and 12 mg/dL (EG). Follow-up analyses occurred in 9 MeOH patients (52.9%, 15 tests) and 15 EG patients (34.9%, 30 tests). Conclusion: This study presents the first confirmatory analytical data on toxic alcohol poisoning among ED patients in Korea, emphasizing ongoing cases around Seoul.